Pengaruh Perbandingan Oat Instan dan Pisang Mas (Musa acuminata) Terhadap Karakteristik Pancake Gluten Free - Levana, Levana; Ari Yusasrini, Ni Luh; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i03.p15, 2023)
This study was to ascertain the impact of comparing instant oats and banana (Musa acuminata) on the quality of gluten-free pancakes as well as the optimum comparison of quick oats and banana mas to generate the greatest quality of gluten-free pancakes. The experimental design was a randomized design with factors, specifically the comparison of instant oats and banana, consisting of five level, namely: 30%: 70%; 40%: 60%; 50%: 50%; 60%: 40%; and 70%: 30%. The expiremented open three repeat were given in order to get the fifteen experimental units. The data obtained were analyzed of variance (ANOVA) in the SPSS program (SPPS 25) and if there has significant effect between treatments, it was continued with Duncan's Multiple Range Test (DMRT). Parameters observed in this study include moisture content, ash content, protein content, crude fiber content, and sensory evaluation test. The treatment had a significant effect on moisture content, ash content, protein content, crude fiber content, hedonic color, texture, taste, overall acceptance, and color and taste scoring. The P4 treatment, namely the ratio of 60% instant oats and 40% banana mas, produced gluten-free pancakes with the best characteristics with the criteria of water content of 48.28%, ash content of 1.94%, protein content 7.55%, crude fiber content 3.19%, the color is slightly brown and liked, the aroma liked, the taste is slightly banana and liked, the texture is liked, and the overall reception is liked.